The peoples' sermon : preaching as a ministry of the whole congregation - Hannan, Shauna K. (Shauna Kay) (Working preacher, 2021)
"The proclamation of the gospel is not a solo endeavor. It is a communal practice, the responsitiblity of the baptized rather than the privilege of the ordained. In The peoples' sermon, Shauna K. Hannan argues that it is no longer faithful for a preacher to craft a sermon in isolation, step into the pulpit (literally or metaphorically) on Sunday morning, offer a monologue, and on Monday start all over, alone, preparing for the following Sunday. Hannan's goal is to create vital worshipping communities where all know and live out their roles in the preaching ministry of the congregation, where both clergy and laity are empowered and equipped in their roles before, during, and after the sermon."--back cover.